Temporomandibular disorders in children and its relation to artificial lactation with bottle-feeding - Espinosa-De Santillana, Irene (2020)
Objective. To establish the relationship of temporomandibular disorders (TMD) in children aged 8 to 10 years, with exclusive artificial feeding. Methods. Case-control study (matched by age and sex). 38 children were included, without growth disturbances or severe oral parafunctions, with prior informed consent (mothers) and assent (children). Participants were diagnosed with TMD (19 cases) or without TMD diagnosis (19 controls) using the Diagnostic Criteria for TMD (CD / TMD), after standardization by the researcher; kappa inter 0.98 and intraobserver 0.73. The history of breastfeeding was recorded with an express questionnaire: type and time of administration, and general data of the child and the mother. Descriptive and inferential statistics were calculated; Chi square analysis was performed to identify the association between TMD and exclusive artificial feeding, and odds ratio (OR), with a significant value of ≤0.05. Results. Age 8.95 ± 0.84 years, 57.9% male, with no differences in age or education of the mother between groups (p> 0,05). The most common type of TMD was muscle pain (57.9%), followed by disc luxation with reduction and combination (21.1%). The mean mouth opening, muscle and joint pain sites were statistically different between cases and controls (p <0.05). The percentage of exclusive artificial feeding was the same in both groups (57.9% p = 1.00), the calculated OR was 1 with a 95% CI of 0.27-3.60. Conclusions. Artificial feeding with the use of a bottle was not related to TMD. The most common type of TMD was muscle pain.